Enhanced recovery after surgery for gastric cancer (ERAS-GC): optimizing patient outcome - Desiderio, Jacopo; Trastulli, Stefano; D’Andrea, Vito; Parisi, Amilcare (Translational Gastroenterology and Hepatology; Vol 5 (January 2020): Translational Gastroenterology and Hepatology, 2019)
Significant advances were achieved, in last decades, in the management of surgical patients with gastric cancer. This has led to the concept of enhanced recovery after surgery (ERAS) with the objective of reducing the length of hospital stay, accelerating postoperative recovery and reducing the surgical stress. The ERAS protocols have many items, including the pre-operative patient education, early mobilization and feeding starting from the first postoperative day. This review aims to highlight possible advantages on postoperative functional recovery outcomes after gastrectomy in patients undergoing an ERAS program, current lack of evidences and future perspectives.